Sustainable transformation at family farming fairs in Gurupi: Using PANC as a source of food and income (Research, Society and Development, 2023)
Modern society imposes several habits on the population, including food habits, in which a small group of vegetables dominates the market, not only in Brazil, but also on a global scale. To this end, the cultivation of other food species is necessary, in this sense, non-conventional food plants emerge as an alternative to meet Brazilian nutritional demand, especially with regard to serving the most vulnerable populations. Furthermore, the consumption of these vegetables is justified because they have low production costs and have rudimentary characteristics: easy handling and high prolificity in adverse environmental conditions, and in many cases they are categorized as weedy plants The objective of this research is to measure the knowledge of the population of Gurupi in relation to PANC, through commercialization and consumption in open fairs markets. The research consisted of semi-structured interviews carried out with stallholders in the municipality of Gurupi-TO, at the farmer's market, in the city center. The methodology adopted is a case study, where four fairs were visited, on different days of the week. Data analysis made it possible to measure the presence of the plants researched on the stalls of the fairs visited, as well as the vegetables most demanded by the population. At the end of the research, it was possible to observe that, in relation to the negotiation of vegetables, conventional vegetables are sold more. And among the best-known PANC with the greatest demand, Mastruz stands out. However, the information acquired also highlights the need for more improved studies in relation to the eating habits of the population of the aforementioned municipality.